ANALISIS PROKSIMAT KARBON AKTIF LIMBAH SERAT SAGU TERAKTIVASI KOH - Nurmalasari; Risna; Surianti; Diana; Afni Mulyasari (Universitas Cokroaminoto Palopo, 2020)
Research on the proximate carbon analysis of sago fiber waste has been carried out. This study aims to determine the chemical properties of sago fiber activated carbon. Activated carbon was prepared using the hydrothermal cabonization method. Activation is carried out chemically using KOH and followed by calcination at a temperature of 500°C. Proximate analysis was carried out to determine the chemical properties of the carbon produced. In this study, the water, ash, volatile and bonded carbon content were 6.67%, 21.22%, 17.8% and 45.79%, respectively.